The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10238-009-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of sibutramine versus sibutramine plus metformin in obese women

Abstract: Sibutramine and metformin are drugs commonly used to obtain weight loss. We aimed to compare the effects of sibutramine alone with that of sibutramine plus metformin combination on weight loss, insulin sensitivity, leptin and C reactive protein in obese women. Seventy obese women were included. After a diet period of month (baseline), each individual was randomly assigned to receive 15 mg sibutramine (sibutramine group; n = 36) or 15 mg sibutramine plus 1,700 mg metformin per day (sibutramine plus metformin gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
1
10
0
3
Order By: Relevance
“…Love-Osborne et al (10) compared weight changes in obese multiethnic adolescents and observed no group differences between metformin and placebo in weight loss measures, whereas other investigators showed a modest decrease in weight and BMI in obese adolescents with normal glucose tolerance treated with metformin vs. placebo (9, 12, 14, 40). However, several recent studies in women with obesity, T2D, and polycystic ovary syndrome, and first-degree relatives of patients with T2D, for example (4148), have also shown a relative lack of efficacy of metformin in normalizing measures of inflammation (hsCRP) or thrombosis (fibrinogen) similar to our findings here. Even in the diet/exercise group, the changes were modest and the intervention improved, but did not normalize the values as compared to normal children.…”
Section: Discussionsupporting
confidence: 89%
“…Love-Osborne et al (10) compared weight changes in obese multiethnic adolescents and observed no group differences between metformin and placebo in weight loss measures, whereas other investigators showed a modest decrease in weight and BMI in obese adolescents with normal glucose tolerance treated with metformin vs. placebo (9, 12, 14, 40). However, several recent studies in women with obesity, T2D, and polycystic ovary syndrome, and first-degree relatives of patients with T2D, for example (4148), have also shown a relative lack of efficacy of metformin in normalizing measures of inflammation (hsCRP) or thrombosis (fibrinogen) similar to our findings here. Even in the diet/exercise group, the changes were modest and the intervention improved, but did not normalize the values as compared to normal children.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the unclear effects of metformin on inflammatory markers, it should be emphasized that metformin is not currently recommended for the management of obesity. Moreover, a recent study in nondiabetic obese women showed that sibutramine monotherapy reduced hsCRP levels and that adding metformin to sibutramine did not result in any additional decrease in hsCRP levels [ 147 ].…”
Section: Antiobesity Agentsmentioning
confidence: 99%
“…However, they did not find any significant changes in these peptides when administered for 6 months to obese women.While a few studies reported a reduction in leptin levels dependent on weight loss, no significant change was observed even with a decrease in body fat [33]. Studies have also shown that changes in serum leptin levels were not statistically significant even after 3, 9 and 12 months of sibutramine administration [34,35]. Bush et al [36] have shown no effect of chronic sibutramine treatment on ghrelin levels in obese mice.…”
Section: Discussionmentioning
confidence: 99%